The Effect of Jigsaw Cooperative Investigation Learning Design toward Team Work Skill and Individual Improvement System of High School Student - Aditya Wardana; Muzzazinah Muzzazinah; Nurmiyati Nurmiyati (PAEDAGOGIA, 2019)
The purpose of this study is to investigated the effect of Jigsaw Cooperative Investigation learning design toward team work skill and individual improvement system of high school student. Quasi experimental research design with quantitative approach was employed for this study. The study was designed using posttest only control group design. The population of this study was grade XI students at SMA Negeri 4 Surakarta  in academic year 2018/2019 consisting of seven classes. Two classes were chosen as a sample using cluster random sampling. Learning was carried out in two classes by applying the jigsaw cooperative investigation learning design in experiment class and conventional grup learning design in control class. Data collection techniques was done by using observation, writen test and document analysis. Normality and homogenity test were performed as a requirement of hypothesis test while the hypotheses it self were tested at 0.05 level of significance using Independent Sample t Test. Data analysis assisted with SPSS 17. The study procedure consists of three steps: planning, implementation and data analysis. The conclusion of this study show that  the application of Jigsaw Cooperative Investigation learning design has significant effect toward team work skill and Individual Improvement System of high school student. It is indicated from p-value of team work skill 0.000 and Individual Improvement System 0.000 less than 0.05 significance level.